Modification of polysulfones by click chemistry: Zwitterionic graft complex and their antiprotein fouling property. Issue 4 (23rd August 2014) - Xu, Canhong; Gu, Shaojin; Huang, Jingjing; Xu, Weilin; Xia, Huan; Du, Jiehao; Liu, Hongtao; Yang, Hongjun; Zhou, Yingshan; Bai, Zikui
ABSTRACT A new nonspecific protein antifouling polysulfone (PSU) material has been elaborated by grafting zwitterionic sulfobetaine (SB) complex by the means of PSU azidation (PSU‐N3) followed by "Click‐Chemistry" with acetylenic zwitterionic SB monomer (N, N'‐diethyl‐N‐propargyl‐N‐ (3‐sulfopropyl) ammonium (DEPAS)). Azidation (PSU‐N3) and functionalization (PSU‐g‐DEPAS) PSU materials were characterized by 1H NMR, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Contact angle and protein adsorption on PSU‐g‐DEPAS and unmodified PSU membrane were studied. The results show that the chemical modification of PSU improved both the hydrophilicity and antiprotein absorption ability. This new fouling‐resistance to protein material has potential for biomaterials applications. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41327.